1968
DOI: 10.1172/jci105934
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and rate of secretion of aldosterone in the bullfrog

Abstract: A study of the metabolism of aldosterone in the bullfrog was undertaken to provide a measurable metabolite for the indirect isotope dilution technique for measuring secretory rates. The rate of excretion of labeled aldosterone was considerably slower in the frog than in man and made necessary the collection of excretory products for 5 days to insure reasonably complete recovery of metabolites. The major identifiable metabolite was a tetrahydro derivative subsequently identified as 3,f-hydroxy-5,8-tetrahydroald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…100) Furthermore, the species difference in the relevant enzyme activity may result in the preferential formation of these conjugates. Glu conjugates were detected for the metabolism of phenytoin in R. pipiens, 113) cypermethrin in liver homogenates of R. temporaria, 82) and aldosterone in R. catesbeiana, 118) while Sulf ones were predominant for T 3 in R. catesbeiana, 119) pyrene, 92) tetrabromobisphenol A 95) and phenols 99) in X. laevis. In contrast to the oxidation and conjugation reactions as above, other metabolic pathways have scarcely been reported.…”
Section: Metabolism Of Chemicals Including Pesticidesmentioning
confidence: 98%
See 1 more Smart Citation
“…100) Furthermore, the species difference in the relevant enzyme activity may result in the preferential formation of these conjugates. Glu conjugates were detected for the metabolism of phenytoin in R. pipiens, 113) cypermethrin in liver homogenates of R. temporaria, 82) and aldosterone in R. catesbeiana, 118) while Sulf ones were predominant for T 3 in R. catesbeiana, 119) pyrene, 92) tetrabromobisphenol A 95) and phenols 99) in X. laevis. In contrast to the oxidation and conjugation reactions as above, other metabolic pathways have scarcely been reported.…”
Section: Metabolism Of Chemicals Including Pesticidesmentioning
confidence: 98%
“…The reductive pathways were indirectly speculated from the formation of N-acetyl products of 4-nitrophenol 99) and a 3β-OH-5β-tetrahydro derivative of aldosterone. 118) Reductive dechlorination and dehydrochlorination were known for DDT in a few species. 24,120) Both oxidative and reductive metabolism were observed in female P. kl.…”
Section: Metabolism Of Chemicals Including Pesticidesmentioning
confidence: 99%
“…Carstensen et al (1959Carstensen et al ( , 1961 reported a fourfold greater increase in aldosterone than in corticosterone pro¬ duction after stimulation by mammalian ACTH or by a saline pituitary extract in the bullfrog adrenal in vitro ; Kraulis & Birmingham (1964) reported similar results in R. pipiens. The corticosteroidogenic effect of ACTH on the amphibian adrenal has also been demonstrated in vivo (Johnston et al 1966(Johnston et al , 1967Ulick & Feinholtz, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosterone and aldosterone are the major corticosteroids secreted by the adrenal glands of many species of amphibians, reptiles and birds, including the American bullfrog, Rana catesbeiana (Carstensen et al 1959(Carstensen et al , 1961Ulick & Solomon, 1960 ;Ulick & Kusch, 1960 ;Nicolis & Ulick, 1965 ;Macchi & Phillips, 1966 ;Psychoyos et al 1966;Johnston et al 1967;Ulick & Feinholtz, 1968), the leopard frog, R. pipiens (Kraulis & Birmingham, 1964), the edible frog, R. rugulosa (Chan et al 1969), the marine toad, Bufo marinus (Crabbé, 1963(Crabbé, , 1966, the turtles, Pseudemys cripta elegans, Chrysemys pietà pietà (Sandor, Lamoureux & Lanthier, 1965;Macchi & Phillips, 1966) and Emys orbicularis (Macchi & Phillips, 1966), the snakes, Natrix natrix (Phillips, Chester Jones & Bellamy, 1962) and Naja naja (Huang et al 1969) the chicken, Gallus domesticus (de Roos & de Roos, 1963Hall & Koritz, 1966) the gull, Larus argentatus (Macchi & Brown, 1964) and the duck Anas platyrhynchos (Sandor & Lanthier, 1963;Macchi & Brown, 1964;Whitehouse & Vinson, 1967). The present study shows that the major corticosteroids produced by the adrenal of Xenopus in vitro are aldosterone, 18-hydroxycorticosterone, corticosterone and 11-deoxycorticosterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation